PERBANDINGAN MOTIVASI BELAJAR MATEMATIKA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN TALKING STICK DAN MAKE A MATCH SISWA KELAS X MAN 1 PADANGSIDIMPUAN - Siregar, Rahma Hayati (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2022)
This research is motivated by the learning carried out by the teacher is still centered on the teacher. The strength and weakness of the motivation to learn mathematics will affect success in learning, so motivation needs to be cultivated, especially within and from outside by providing a fun learning model so that students are motivated to learn mathematics. The formulation of the problem is How is the students' motivation to learn mathematics using the Talking Stick learning model?, How is the students' motivation to learn mathematics using the Make A Match learning model?, Are there differences in students' motivation to learn mathematics using the Talking Stick learning model and the Make A Match learning model?. This study uses a quasi-experimental method involving two groups, namely the experimental class I using the Talking Stick learning model and the experimental group II using the Make A Match learning model. The research design used in this study is The Non Equivalent Control Design. The experimental group I used the Talking Stick learning model and the experimental group II used the Make A Match learning model. The data analysis used was descriptive and inferential statistical formulas, namely normality, homogeneity and hypothesis testing with paired sample t-test. Based on the results of the hypothesis test of the average value, there are differences in the learning motivation of students in the class using the Talking Stick model and the class using the Make A Match model. But this difference is not significant seen from the value of Sig. (2-tailed) of 0.843 > 0.05, it can be concluded that there is no significant (significant) difference between the average mathematics learning motivation of students who are taught using the Talking Stick learning model and using the Make A Match learning model.